1996
DOI: 10.1002/jmri.1880060310
|View full text |Cite
|
Sign up to set email alerts
|

Contrast enhancement with GD‐EOB‐DTPA in MR imaging of hepatocellular carcinoma in mice: A comparison with superparamagnetic iron oxide

Abstract: The purpose of this study was to evaluate the ability of the new liver-specific magnetic resonance contrast agent gadolinium-ethoxybenzyl-diethylenetriamine penta-acetic acid (Gd-EOB-DTPA) to detect hepatocellular carcinoma (HCC). Seventeen mice with 66 chemically induced HCCs underwent magnetic resonance imaging with both Gd-EOB-DTPA (30 mumol/kg) and superparamagnetic iron oxide (SPIO; 10 mumol/kg). After enhancement, lesion-to-liver contrast-to-noise ratios (CNRs) of 47 detected HCCs increased negatively fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
17
0

Year Published

1997
1997
2011
2011

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 35 publications
(19 citation statements)
references
References 28 publications
2
17
0
Order By: Relevance
“…Recently, Narita et al (21) reported that hyperintense lesions were found in 6 of 22 HCCs, in which all cases were moderately differentiated. Our study showed no correlation between tumor differentiation of an HCC and the uptake of gadoxetic acid as previously reported (11,20,21). Based on these results, we think that, in clinical practice, gadoxetic acid-enhanced hepatobiliary-phase images should not be used to predict the exact extent of tumor differentiation.…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…Recently, Narita et al (21) reported that hyperintense lesions were found in 6 of 22 HCCs, in which all cases were moderately differentiated. Our study showed no correlation between tumor differentiation of an HCC and the uptake of gadoxetic acid as previously reported (11,20,21). Based on these results, we think that, in clinical practice, gadoxetic acid-enhanced hepatobiliary-phase images should not be used to predict the exact extent of tumor differentiation.…”
Section: Discussionsupporting
confidence: 66%
“…[Color figure can be viewed in the online issue, which is available at wileyonlinelibrary.com.] Table 2 Comparison of MR Findings Between Non-hypointense and Hypointense Areas of Hepatocellular Carcinomas on Gadoxetic AcidEnhanced Hepatobiliary-Phase MR Imaging moderately to poorly differentiated HCCs was reported (20). In human studies, Huppertz et al reported two of four highly differentiated HCCs that exhibited exceeding or equal uptake in comparison to the surrounding parenchyma, and no uptake in moderately or poorly differentiated HCCs (3).…”
Section: Discussionmentioning
confidence: 99%
“…In our animal model, it was impossible to perform scans under breath-holding. Therefore, our study showed results under the conventional scanning protocols at currently available field strength (1). Rapid scans such as T2-weighted fast spin echo and multislice T1-weighted gradient echo pulse sequence also should be included in human studies (19)(20)(21).…”
Section: Discussionmentioning
confidence: 89%
“…They also suggested that Gd-EOB-DTPA might be of value in tissue characterization because the positive enhancement appeared only in highly differentiated HCCs (6). However, in our previous study, several HCCs, both highly differentiated and moderately differentiated, were positively enhanced (7).…”
mentioning
confidence: 94%